A new method for measuring pistoning in lower limb prosthetic - Gholizadeh, H.; Abu Osman, Noor Azuan; Luviksdottir, A.G.; Kamyab, M.; Eshraghi, A.; Ali, S.; Wan Abas, Wan Abu Bakar (2011)
The quality of suspension in lower limb prosthetics has significant role in amputee's satisfaction. Good suspension lessens the pistoning movement of the residual limb inside the prosthetic socket. A number of methods are used for measuring pistoning; however most of them are difficult to be performed inside the prosthetic clinic and by every prosthetist. The purpose of this study was to introduce a new simple method for measuring pistoning in Transtibial prosthesis in static position. This method was developed in-house at Össur for the first time. In this study we used this technique to measure pistoning between socket and liner in three subjects. The result showed that this method can be an alternative method for measuring pistoning. Moreover, that makes it simple for prosthetists to test pistoning in the clinic and is a safe method for the subject. © 2011 Springer-Verlag.